Factors Affecting Avifaunal Diversity in Selected Agro-Ecosystems of Himachal Pradesh Agricultural University, Palampur, Himachal Pradesh, India - J. D. Kottawa-Arachchi; G. Thakur; A. Dwivedi; R. Tshering; H. M. Samimi; Y. Chaudhary; H. K. Chaudhary (Zoodiversity, 2022)
Avifaunal diversity in eight different habitats of Himachal Pradesh Agricultural University, Palampur was studied in order to find factors affecting the occurrence of bird species. Bird populations were sampled in different agro-ecosystems such as farm fields (experimental and organic), wetland, abandoned tea plantation, administration area, playground, secondary forest and stream vegetation. A total of 125 species of birds belonging to 51 families, including 33 winter visitors and 27 summer visitors have been recorded. Among them, 78 insectivores followed by 18 carnivores were recorded. The abandoned tea field was a diverse habitat that maintained the highest species richness recording 50 species, followed by stream vegetation and organic farm. Seasonal variations and habitat heterogeneity play crucial role in shaping species richness. Plant diversity, vegetation structure and microhabitats support different feeding guilds, temporary refuge and migratory route which result in increased bird diversity. Based on different categories of birds, the cluster analysis revealed three distinct clusters of habitats, first cluster containing administration area and secondary forest habitats, experimental farm and wetland grouped in cluster II, whereas cluster III contained habitats viz. abandoned tea plantation, playground, organic farm and stream vegetation. Several conservation measures such as increasing plant diversity, conducting regular and long-term systematic studies, introducing bird friendly management plan are recommended to conserve and enhance avifaunal diversity in the university.